Pelayanan Kesehatan Dengan Latihan Deep Breathing Exercise Terhadap Peningkatan Konsentrasi Belajar Siswa SMA Negeri 64 Cipayung - Mohammad Ali; Abdurahman Berbudi Bowo Laksono; Roikhatul Jannah (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2022)
Concentration of learning is the concentration of thoughts and attention on the information obtained by a person during the learning period. Good concentration is if a person is in a relaxed state without any stress which is characterized by an open mind. Concentration of learning is a source of mind power that works based on memory. In learning, concentration is needed in the realization of focused attention on a lesson. Concentration is one aspect of supporting students to achieve good performance. If concentration is reduced, attending lessons in class and studying privately can be disrupted. Symptoms due to decreased concentration levels of students due to lack of energy intake to the brain can be seen when students are easily bored and easily feel sleepy. Therefore, we carry out community service activities to help students concentrate on learning, by providing deep breathing exercises, it is found that there is an increase in student concentration at SMAN 64 Cipayung. Keywords: Deep Breathing Exercise, Student Learning Concentration.